Upaya Peningkatan Pemahaman Mahasiswa Akuntansi Politeknik Negeri Semarang dalam Memahami Artikel Internasional - Maharani Rona Makom (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
One of the educational problems that occur in Indonesia is the low interest in reading of students, especially the ability to read foreign language texts that are still low. This service activity aims to improve the understanding of accounting students of Politeknik Negeri Semarang in understanding international articles. The implementation of the activity was carried out by the author in the work unit of the Politeknik Negeri Semarang, Department of Accounting. There are 4 activities carried out from the 1st to the 30th of August 2020, namely; 1) Pre-Test reading habits and understanding of students in reading and understanding international articles, 2) Creating teaching materials for virtual tutorials and simulations of reading international articles, 3) Creating international article analysis assignment procedures, 4) Post Test of reading habits and student understanding in reading and understanding international articles. The activity was attended by final semester students of the finance and banking study program with 71 participants from KP 3A, 3B, and 3C classes. During the implementation of the activity the author received support from superiors, fellow lecturers, students and education personnel in the Accounting Department so that all activities could be completed.